2019
DOI: 10.14527/pegegog.2019.019
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of students' strategies for doing science homework by parental support and students' goal orientation

Abstract: The aim of this study is to examine how parents’ support for their children’s science homework and the goal orientation of students in science homework predict their deep learning and management strategies that students use when doing homework. For this purpose, among quantitative research approaches, correlational method was used in the study. The sample of the study consisted of 328 middle school students enrolling in public schools in Erzurum. As data gathering tools, the Parental Homework Support Scale, Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Parental controlling actions (dictating schedules, giving unasked for advice) are negatively related to children's outcomes (Núñez et al 2015); however, this may be due to children who are struggling in school needing more parental direction and help (Cooper, Lindsay, and Nye 2000), rather than being a simple byproduct of parental actions. Other reviews of the literature show definite positive effects of parental engagement in homework, including students' views of their abilities in relation to learning (Rogers et al 2014;Kurt and Taş 2019). Taken as a whole, research suggests strongly that when parents are appropriately, helpfully involved in children's homework, children do more of that homework and benefit more from the learning involved, in terms of achievement, confidence, life skills (time management, self-regulation) and academic selfconcept (Núñez et al 2015).…”
Section: Parental Attributes For Masterymentioning
confidence: 98%
See 3 more Smart Citations
“…Parental controlling actions (dictating schedules, giving unasked for advice) are negatively related to children's outcomes (Núñez et al 2015); however, this may be due to children who are struggling in school needing more parental direction and help (Cooper, Lindsay, and Nye 2000), rather than being a simple byproduct of parental actions. Other reviews of the literature show definite positive effects of parental engagement in homework, including students' views of their abilities in relation to learning (Rogers et al 2014;Kurt and Taş 2019). Taken as a whole, research suggests strongly that when parents are appropriately, helpfully involved in children's homework, children do more of that homework and benefit more from the learning involved, in terms of achievement, confidence, life skills (time management, self-regulation) and academic selfconcept (Núñez et al 2015).…”
Section: Parental Attributes For Masterymentioning
confidence: 98%
“…This paper suggests moving children away from an orientation on external validation for their learning processes (which would be evident, for example, in asking parents to check and monitor homework), to an orientation on(Kurt and Taş 2019) internal validation, through increased confidence in their abilities to learn, and the acquisition of and confidence in the skills needed to do so. Children with a 'mastery orientation' toward learning will value learning for its own sake; they are also likely to structure their work effectively (Kurt and Taş 2019). This is not to deny the importance or validity of external measures of learning, such as marks, grades and exam results.…”
Section: Mastery Orientationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (e.g., Bell & St. Clair, 2015;Eisenberg et al, 2010;Kurt & Taş, 2019;Quiley et al, 2011) have found that providing an interest in science in early childhood strengthens children's learning of science content. For example, Fragkiadaki and Ravanis (2021) pointed out that a child's emotions in participating in, contributing to, or being in scientific activities or environments have a crucial role in examining and understanding children's early learning and development related to science.…”
mentioning
confidence: 99%